Prescriber Aimed Intervention to Optimize Opioid Prescribing Patterns After Intracranial Surgery: Addressing the Nation's Opioid Epidemic and Decreasing the Neurosurgeon's Narcotic Footprint. (1st September 2019) - Asmaro, Karam P; Haider, Sameah A; Chandra, Ankush; Telemi, Edvin; Mansour, Tarek R; Zakaria, Hesham M; Robin, Adam M; Lee, Ian Y; Air, Ellen L; Rock, S Jack P; Kalkanis, Steven N; Schwalb, Jason M
Abstract: INTRODUCTION: Opioids are prescribed routinely after cranial surgery despite a paucity of evidence regarding the optimal quantity to dispense. While pain control is essential acutely, opioid need for subacute recovery remains controversial. Over-prescribing may adversely contribute to the epidemic of opioid abuse, chronic use, and diversion. The aim of this study is to evaluate the effectiveness of a system-wide campaign to reduce opioid prescribing excess while maintaining adequate analgesia and patient satisfaction. METHODS: Patients undergoing intracranial surgery for tumor with home disposition were identified from June 2017 to December 2018. Patients were stratified as those discharged before and after the intervention which consisted of developing departmental consensus guidelines, provider coaching, and ongoing reinforcement. We queried the amount of opioids prescribed at discharge measured in morphine milligram equivalents (MME), preoperative opioid intake, pain scores before and after discharge, and total opioid intake 24-hr before discharge in addition to procedure-specific variables. RESULTS: A total of 238 consecutive home discharges were examined (mean age: 52.7 yr; 129 men [54%]). Following a 2-mo educational period, the quantity of opioids prescribed decreased by 48% in the craniotomy group (n = 203; median MME [IQR], 225 [109-450] vs 108 [0-240], P < .00002) in addition to refill requests (17% vs 7.6%, P = .047) despite both groups having similar baseline pain scores on discharge. Pain scores remained satisfactory at outpatient follow-up (1.23 vs 0.85, P = .17). Similar results were observed in the burr hole group (n = 35) where the quantity of opioids prescribed decreased by 67% (median MME [IQR], 225 [109-450] vs 10 [0-187.5], P = .06) with no consequent increase in refill requests, follow-up pain scores, or patient dissatisfaction. CONCLUSION: Opioids may be overprescribed postoperatively, however, we were able to achieve a dramatic reduction in opioids prescribed without affecting refill requests, patient satisfaction, or perceived analgesia. More studies are needed to optimize postoperative pain control while reducing superfluous narcotic disbursement.